Vertical Distribution of Silica Content Based on Drill Hole Depth in a Nickel Laterite Deposit, Towara Village, North Morowali, Indonesia - Difri Candra A.N; Muhammad Ihsyam (Journal of Green Chemical and Environmental Engineering, 2025)
This study aims to observe the relationship between SiO₂ content and Ni content with variations in the depth of laterite nickel production in the Towara area. The independent variable was nickel extraction at depths of 1, 5, 10, and 15 meters from four drill holes spaced 100 meters apart. The dependent variable was nickel ore samples. Samples were obtained through drilling activities, followed by wet and dry preparation, including size reduction, drying, grinding to 200 mesh, and pelletization, before being analyzed using XRF according to the JIS M-8109-1996 standard. The results of the study showed a negative relationship between SiO₂ content and Ni content. A depth of 10 meters had the highest Ni content of 1.977 % at a medium SiO₂ content of 33.577 %. A depth of 15 meters showed a very high SiO₂ content (>66%) with a low Ni content (<0.3 %). The Limonite and Saprolite zones dominated the interval with high Ni content, while the Bedrock and Below Laterite Deposit zones were dominated by high SiO₂ and low Ni content. An increase in silica content at a certain depth indicates a decrease in nickel enrichment potential, making silica an important parameter in evaluating nickel prospect zones.